Flaws and Defects in Crystals - V. Basil Hans (International Journal of Crystalline Materials, 2025)
Crystalline materials are defined by their long-range atomic order; however, no real crystal is completely free from imperfections. This article provides a comprehensive overview of the various types of crystal defects and imperfections that occur in solid materials and their significant influence on material properties. Point defects, including vacancies, interstitials, and substitutional atoms, are examined alongside line defects such as edge and screw dislocations, as well as planar defects encompassing grain boundaries, stacking faults, and twin planes. The discussion highlights how these imperfections affect mechanical strength, electrical conductivity, thermal properties, and diffusion behavior. Special emphasis is placed on the role of dislocations in facilitating plastic deformation and how defect interactions determine material toughness and ductility. Furthermore, the concept of defect engineering is explored as a strategic approach to tailor materials for specific applications. Through controlled manipulation of defect structures, scientists and engineers can enhance the performance of semiconductors, metallic alloys, and advanced ceramics. The review also examines recent developments in the characterization and computational modeling of defects, which have deepened understanding of their dynamics and formation mechanisms. Overall, this study underscores the crucial role of crystal defects in determining the functional and structural properties of materials, emphasizing their importance in both natural crystalline systems and engineered materials for modern technological applications.
Keywords: Defect engineering; Material properties; dislocations; grain boundaries; point defects